Utility of Kappa and Lambda Immunofluorescence to Evaluate Plasma Cell Dyscrasias on Renal Biopsies - Pant, Anil Dev; Amatya, Manim; Shah, Dibya Singh; Pahari, Bishnu; Joshi, Upendra; Sayami, Gita; Karki, Shovana (Grande Medical Journal, 2025)
Background: Routine assessment of renal biopsies requires staining with Congo Red staining for amyloidosis as well as immunofluorescence staining for kappa and lambda to detect monoclonal gammopathies. Correlating with histopathology, we can diagnose the nature of renal involvement of plasma cell dyscrasias, which may be in the form of myeloma cast nephropathy, light chain deposition disease, interstitial nephritis, and toxic tubulopathy. If there is nodular glomerulosclerosis which may resemble diabetic kidney, combination of Congo Red and kappa/lambda can be helpful in diagnosis of AA vs AL amyloidosis. Method: On retrospective analysis of all renal biopsies received over 2017-2024, a total of 12 cases were finalized out of 824 total renal biopsies. The biopsies had undergone the usual processing with routine stains and immunofluorescence studies. Cases were diagnosed with the help of clinical features, biochemical findings, histopathological analysis and immunofluorescence studies. Result: Patients with either amyloidosis or kappa/lambda monoclonality were more commonly males with median age of 62.5 years and increased creatinine level. Nephrotic syndrome was the most common clinical presentation. Myeloma cast nephropathy, light chain deposition disease and nodular amyloidosis were the most common histopathological diagnoses and lambda was more commonly predominant on immunofluorescence. Conclusion: Immunofluorescence with kappa/lambda is essential in the diagnosis of renal involvement by myeloma which may precede, occur simultaneously, or follow bone marrow involvement.